Improving test scores in five easy steps : the silver bullet - Quinn, Gary W., 1955- (Rowman & Littlefield Education, 2010)
Through the chapters in this book, a plan will be outlined, that if followed, will improve test scores in any school district. The amount of improvement will be determined by various variables including present level of achievement, previous implementation of some of these concepts, the level of implementation, the vision from the top and the focus on the plan.